Temporal Clustering of Hate Crimes in the Aftermath of the Brexit Vote and Terrorist Attacks: A Comparison of Scotland and England and Wales - Piatkowska, Sylwia J. (The British journal of criminology, 2021)
This study examines the temporal clustering of hate crimes in Scotland, England and Wales in the wake of the Brexit vote and the 2017 terrorist attacks. Using an interrupted time-series design, we analyzed hate crime data by motivation type and month as provided by area police forces under the Freedom of Information Act. The results revealed a significant increase in crimes based on religious bias in Scotland, England and Wales after the 2017 terrorist attacks. There is also evidence of a significant increase in racial hate crime in the aftermath of the European Union referendum but only in England and Wales. We suggest that these findings underscore the role of political legitimization in predicting hate crimes.